2022
DOI: 10.1002/nop2.1497
|View full text |Cite
|
Sign up to set email alerts
|

Registered nurses' perceptions of their roles in medical‐surgical units: A qualitative study

Abstract: Aim The aim of this study was to gain insight into the perception of nurses about their roles in medical‐surgical units. Background As a result of ever‐changing work environments, medical‐surgical nurses find it difficult to know and practice according to the full scope of their roles. Design A qualitative descriptive study. Methods Semi‐structured individual interviews were conducted with 21 nurses on three campuses of a large tertiary care hospital located in Quebec, Canada. Thematic analysis was used to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…A previous study by Nazon et al. (2023) confirms patient safety risks caused by a lack of resources and their consequences; when workload increases, the risk of misjudgement also increases. Previous scientific evidence also highlights those four patients per nurse versus six patients per nurse is associated with better patient outcomes, such as fewer hospital‐associated infections, shorter length of stay, fewer readouts, higher patient satisfaction and lower rates of nurses experiencing burnout (Coster et al., 2018; McHugh et al., 2021).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…A previous study by Nazon et al. (2023) confirms patient safety risks caused by a lack of resources and their consequences; when workload increases, the risk of misjudgement also increases. Previous scientific evidence also highlights those four patients per nurse versus six patients per nurse is associated with better patient outcomes, such as fewer hospital‐associated infections, shorter length of stay, fewer readouts, higher patient satisfaction and lower rates of nurses experiencing burnout (Coster et al., 2018; McHugh et al., 2021).…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies shown that nurses need to choose between administrative tasks and spending time with patient's bedside, and our findings are similar. This is described in the literature as an internal conflict of nurses due to their own demands and the goal of being a good nurse (Furåker, 2009; Nazon et al., 2023; Suhonen et al., 2018; Yngman‐Uhlin et al., 2016). The gap between nurses' own demands and reality becomes overwhelming and affects nurses' mental well‐being (Jakobsson et al., 2023; Sastrawan et al., 2019; Suhonen et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study of 60 surgical nurses conducted in an Australian hospital, more than one‐third of nurses did not use clean gloves properly during postoperative surgical wound management, and more than half did not provide postoperative wound management education to patients (Ding et al., 2017). Moreover, surgical nurses struggle to articulate the specific activities they undertake to prevent postoperative complications (Nazon et al., 2023). Overall, nurses' lack of role clarity and variation in practice, may inhibit nurses' ability to influence postoperative outcomes.…”
Section: Introductionmentioning
confidence: 99%